2007
DOI: 10.1002/mus.20723
|View full text |Cite
|
Sign up to set email alerts
|

The effect of eccentric exercise on position sense and joint reaction angle of the lower limbs

Abstract: Impaired position sense and impaired joint reaction angle of the lower limbs after muscle-damaging activities is a serious functional limitation that may lead to an increased risk of injury, particularly in older populations. The purpose of the present study was to examine whether position sense and joint reaction angle to release can be affected by eccentric exercise-induced muscle damage. Twelve women underwent an isokinetic exercise session of the lower limb. Isometric peak torque, delayed-onset muscle sore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 43 publications
4
83
1
1
Order By: Relevance
“…Secondly, the effect of eccentric training might lead to increased tensile strength and tendon hypertrophy. Thirdly, the effect of the stretching component of the eccentric training may have a significant influence on the elastic characteristics of the tendon (Paschalis et al, 2007). In previous studies, Nelson (2006) reported that eccentric training (gain=9.48°) through a full range of motion improved hamstring flexibility better then the gains made by a static stretch group (gain=5.05°) or a control group (gain=-1.08°), and our findings corroborate this.…”
Section: Discussionsupporting
confidence: 87%
“…Secondly, the effect of eccentric training might lead to increased tensile strength and tendon hypertrophy. Thirdly, the effect of the stretching component of the eccentric training may have a significant influence on the elastic characteristics of the tendon (Paschalis et al, 2007). In previous studies, Nelson (2006) reported that eccentric training (gain=9.48°) through a full range of motion improved hamstring flexibility better then the gains made by a static stretch group (gain=5.05°) or a control group (gain=-1.08°), and our findings corroborate this.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, walking is the preferred mode of exercise for many people, including hikers, backpackers, and the elderly population. Previous studies revealed significant impairments in position sense of the lower limbs following eccentric exercise of the knee extensors or flexors (Paschalis et al 2007b(Paschalis et al , 2008Torres et al 2010). Since adequate proprioception is essential for capable and safe human movement, it is possible that impairments in position sense and/or mechanical changes caused by muscle damage and delayed onset of muscle soreness (DOMS) may lead to perturbations in everyday activities, such as walking and increase the risk of more severe musculoskeletal injury.…”
Section: Introductionmentioning
confidence: 98%
“…Per opposition to pre-participation warm-up exercises, high intensity exercise inducing muscle fatigue is associated with reduction of muscle force, joint range of motion and joint stability, and with clumsiness in movements demanding high levels of accuracy (Brockett, Warren, Gregory, Morgan, & Proske, 1997;Howell, Chleboun, & Conatser, 1993;Paschalis, et al, 2007;Proske, et al, 2003;Saxton, et al, 1995). Fatigue is defined as an exercise-induced reduction in the ability of a muscle to generate force or power due to peripheral and/or central factors, related with an increase in perceived exertion, which can be defined as the intensity of subjective effort, strain, discomfort or fatigue sensation that one feels during exercise (Gandevia, 2001).…”
Section: Exercise-induced Muscle Fatiguementioning
confidence: 99%
“…Fatigue is defined as an exercise-induced reduction in the ability of a muscle to generate force or power due to peripheral and/or central factors, related with an increase in perceived exertion, which can be defined as the intensity of subjective effort, strain, discomfort or fatigue sensation that one feels during exercise (Gandevia, 2001). The effects of exercise-induced muscle fatigue on joint proprioception have been extensively investigated in the last decades (Allen & Proske, 2006;Brockett, et al, 1997;Carpenter, et al, 1998;Forestier & Bonnetblanc, 2006;Forestier, Teasdale, & Nougier, 2002;Givoni, Pham, Allen, & Proske, 2007;Ju, Wang, & Cheng, 2010;Lattanzio, Petrella, Sproule, & Fowler, 1997;Lee, Liau, Cheng, Tan, & Shih, 2003;Miura, et al, 2004;Myers, Guskiewicz, Schneider, & Prentice, 1999;Paschalis, et al, 2008;Paschalis, et al, 2007;Ribeiro, Santos, Gonçalves, & Oliveira, 2008;Ribeiro, Venâncio, Quintas, & Oliveira, 2011;Saxton, et al, 1995;Skinner, et al, 1986;Torres, et al, 2010;Tripp, et al, 2004;Vila-Cha, et al, 2011;Walsh, Hesse, Morgan, & Proske, 2004) (Table 4). The majority of studies investigating the effects of exercise-induced fatigue on proprioception have been conducted in the knee joint.…”
Section: Exercise-induced Muscle Fatiguementioning
confidence: 99%